Faktor Yang Berhubungan Dengan Tindakan Tidak Aman Di PT. Perusahaan Listrik Negara (PLN) UPDK Tello (Window of Public Health Journal, 2026)
Occupational safety and health protection is an effort by companies to protect workers while they carry out their work and prevent workplace accidents. Work accidents are generally caused by unsafe behavior factors (unsafe actions) and unsafe conditions. This study aims to determine the factors related to unsafe actions among operator workers at PT PLN (Persero) UPDK Tello in 2023. This study is a quantitative study with a cross-sectional study design. The sampling technique used was total sampling with a sample size of 40 respondents. Data collection was carried out using questionnaires and interviews. Data analysis was carried out univariately and bivariately using the Chi-Square test at a 95% confidence level (α = 0.05). The results showed that there was a significant relationship between attitudes and unsafe actions (p = 0.027) and between work period and unsafe actions (p = 0.020). Meanwhile, there was no significant relationship between knowledge and unsafe actions (p = 0.522), the availability of personal protective equipment (PPE) and unsafe actions (p = 1.000), or supervision and unsafe actions (p = 0.441) among operator workers at PT PLN UPDK Tello in 2023. This study concluded that attitude and tenure were associated with unsafe actions, whereas knowledge, PPE availability, and supervision were not. To improve safety, the company should prioritize fostering positive work attitudes and increasing safety awareness, both of which are key to reducing unsafe actions and workplace accidents.